Identification of Rh alloantibody in Thalassaemia Patients (Journal of Medicine, 2016)
Summary: Thalassaemiais a congenital hemolytic disorder caused by partial or complete deficiency of ? or ? globin chain synthesis. The disease is treated by lifelong red cell transfusion. So they are at high risk of developing allo-antibodies, resulting difficult to obtain compatible blood, results in, haemolysis & occasionally life threatening events.Objectives: To find out the frequency of Rhesus alloantibodies among the thalassaemic patients.Methods: This cross sectional study was done in the department of transfusion medicine in Bangabandhu Sheikh Mujib Medical University from 01-07-2010 to 03-07-2011. Sample size was 100 and the data was collected by face to face interview. Purposive sampling method was applied using inclusion & exclusion criteria. Statically analysis of the result was obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-15) (SPSS Inc, Chicago, IL, USA).Result: In the present study all respondent were Rh D-positive. Out of 100 respondents 2 (2.0%) had positive direct Coombsand 6 (6.0%) had positive indirect Coomds test. Out of 6 respondent with Rhesus all-antibody, 4 (66.7%) had anti E antibody, 1(16.7%) had anti c antibody and 1 (16.7%) had non specific antibody.Conclusion: In this study among the 100 respondents of thalassaemic patients who receive regular blood transfusion 6 (6.0%) had developed rhesus allo-antibody among with the most common was Anti E antibody 4 (66.7%). Such information may enable understanding and prevention of this serious and common complication.J MEDICINE July 2016; 17 (2) : 79-83